Response of Johnsongrass Biotypes from Humid and Subhumid Regions to Nicosulfuron in Argentina - Yanniccari, Marcos Ezequiel (2012)
The response of seven Johnsongrass (Sorghum halepense L. Pers.) biotypes from humid and subhumid regions to reduced rates of nicosulfuron was evaluated. Variability in performance to reduced rates of this herbicide could limit the design and implementation of integrated weed management programs. The three biotypes from subhumid regions were less sensitive to nicosulfuron and differed significantly from the humid biotype with regards to fresh weight, total rhizome length, and number of rhizomes nodes when evaluated 20 weeks after treatment. Consequently, a substantial Johnsongrass re-infestation could occur if rates below one-half of the nicosulfuron labeled rate were used to control Johnsongrass in subhumid regions. These biotypes showed a significant difference in regrowth following reduced rates of nicosulfuron compared to the biotype from the humid region. According to the results of Johnsongrass regrowth, the use of rates below one-half of nicosulfuron labeled rate must be avoided in these environments and the use of nicosulfuron at lower rates is not a viable recommendation.